CLINICAL AND EXPERIMENTAL STUDIES OF METABOLIC THE BODY'S RESPONSE TO CHRONIC EXPOSURE TO COAL ROCK DUST - Baxodirov Behzod Baxodirovich; Xolmurodova Dilorom Bekpo‘latovna; Xolmurotov Baxodir Toshpo‘latovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: Anthracosilicosis in miners is caused by chronic exposure to coal dust and is characterized by the progressive development of the inflammatory process, pronounced lipid metabolism disorders, and an immunodeficiency state. The stages of development were revealed in the experiment anthracosilicosis, according to which adequate methods of prevention and correction of disorders caused by prolonged exposure to coal dust are recommended.